Sustainable Building Assessment of Colonial Shophouses after Adaptive Reuse in Kuala Lumpur - Al-Obaidi, K.M.; Wei, S.L.; Ismail, M.A.; Kam, K.J. (MDPI, 2017)
Kuala Lumpur, as a major capital city, has undergone a drastic transformation in the past ten years. Many heritage buildings have been sacrificed for urban renewal projects. Those located in the touristic heritage zones within Kuala Lumpur were being converted by their owners into hotels and cafés to meet current demands to sustain their incomes. This approach, however, creates several physical and environmental issues within the new adaptation. The aim of this study is to evaluate the building performance of heritage shophouses that were adapted into budget hotels. The research focuses on two case studies in a strategic and historical location of Jalan Sultan, Kuala Lumpur. At the initial stage, interviews and physical surveys were done to determine the context of this study. The authors of this research then used a triangulation method through indoor environmental condition assessment, measurements of indoor environmental conditions and occupant survey to determine the indoor building performance after the adaption. Results showed that adaptive reuse heritage buildings can perform and meet new indoor environmental requirements, but many sensitive design judgments need to be made before the adaptive reuse renovation. The research found that the use of natural light, natural ventilation, recycled materials and water efficiency have been neglected and thus, they should be prioritized and preserved to ensure a successful change of use. Conserving existing heritage buildings, while incorporating new usages with acceptable comfort, is in line with the principle of sustainability.